Population genomics and pathotypic evaluation of the bacterial leaf blight pathogen of rice reveals rapid evolutionary dynamics of a plant pathogen - Song, Zhiwei; Zheng, Jinshui; Zhao, Yancun; Yin, Jiakang; Zheng, Dehong; Hu, Huifeng; Liu, Hongxia; Sun, Ming; Ruan, Lifang; Liu, Fengquan (Frontiers in Cellular and Infection Microbiology, 2023)
The Xanthomonas oryzae pv. oryzae (Xoo) is a bacterial pathogen causing bacterial blight disease in rice, resulting in significant yield reductions of up to 50% in rice production. Despite its serious threat to food production globally, knowledge of its population structure and virulence evolution is relatively limited. In this study, we employed whole-genome sequencing to explore the diversity and evolution of Xoo in the main rice-growing areas of China over the past 30 years. Using phylogenomic analysis, we revealed six lineages. CX-1 and CX-2 primarily contained Xoo isolates from South China, while CX-3 represented Xoo isolates from North China. Xoo isolates belonging to CX-5 and CX-6 were the most prevalent across all studied areas, persisting as dominant lineages for several decades. Recent sporadic disease outbreaks were primarily caused by Xoo isolates derived from the two major lineages, CX-5 and CX-6, although Xoo isolates from other lineages also contributed to these outbreaks. The lineage and sub-lineage distributions of Xoo isolates were strongly correlated with their geographical origin, which was found to be mainly determined by the planting of the two major rice subspecies, indica and japonica. Moreover, large-scale virulence testing was conducted to evaluate the diversity of pathogenicity for Xoo. We found rapid virulence evolution against rice, and its determinant factors included the genetic background of Xoo, rice resistance genes, and planting environment of rice. This study provides an excellent model for understanding the evolution and dynamics of plant pathogens in the context of their interactions with their hosts, which are shaped by a combination of geographical conditions and farming practices. The findings of this study may have important implications for the development of effective strategies for disease management and crop protection in rice production systems.